Rewrite the product using the Distributive Property. Then simplify. 1) 2(4 + 7) 2) 3(1/3 – p)

Question

Rewrite the product using the Distributive Property. Then simplify.

1) 2(4 + 7)
2) 3(1/3 – p)

in progress 0
Mít Mít 2 weeks 2021-09-01T11:25:08+00:00 1 Answers 0 views 0

Answers ( )

    0
    2021-09-01T11:26:18+00:00

    Answer:

    2(4 + 7) = 22

    3(\frac{1}{3} - p) = 1 - 3 p

    Step-by-step explanation:

    Given

    1 & 2

    Required

    Rewrite and simplify

    1.\ 2(4 + 7)

    Apply distributive property

    2(4 + 7) = 2 * 4 + 2 * 7

    2(4 + 7) = 8 + 14

    2(4 + 7) = 22

    2.\ 3(\frac{1}{3} - p)

    Apply distributive property

    3(\frac{1}{3} - p) = 3*\frac{1}{3} - 3 * p

    3(\frac{1}{3} - p) = \frac{3}{3} - 3 * p

    3(\frac{1}{3} - p) = 1 - 3 * p

    3(\frac{1}{3} - p) = 1 - 3 p

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )